2016
DOI: 10.1038/nature16980
|View full text |Cite
|
Sign up to set email alerts
|

Moralistic gods, supernatural punishment and the expansion of human sociality

Abstract: Moralistic gods, supernatural punishment and the expansion of human sociality Benjamin Grant Purzycki 1 , Coren Apicella 2 , Quentin D. Atkinson 3,4 , Emma Cohen 5,6 , Rita Anne Mcnamara 7 , Aiyana K. Willard 8 , Dimitris Xygalatas 9,10,11 , Ara norenzayan 7 & Joseph henrich 7,12,13 Since the origins of agriculture, the scale of human cooperation and societal complexity has dramatically expanded 1,2 . This fact challenges standard evolutionary explanations of prosociality because well-studied mechanisms of coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
291
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 392 publications
(307 citation statements)
references
References 30 publications
10
291
3
3
Order By: Relevance
“…The finding that eyes of negative valence are more successful in enforcing a prosocial norm is readily reconciled with other studies: functional Magnetic Resonance research has corroborated that eyes expressing anger are anxiogenic, heightening arousal [40]. In addition, a recent cross-cultural study shows that people who are reminded of the presence of their respective god show a stronger increase in both trusting and cooperative behavior if they rated their god as more punitive [41].…”
Section: Discussionsupporting
confidence: 51%
“…The finding that eyes of negative valence are more successful in enforcing a prosocial norm is readily reconciled with other studies: functional Magnetic Resonance research has corroborated that eyes expressing anger are anxiogenic, heightening arousal [40]. In addition, a recent cross-cultural study shows that people who are reminded of the presence of their respective god show a stronger increase in both trusting and cooperative behavior if they rated their god as more punitive [41].…”
Section: Discussionsupporting
confidence: 51%
“…S. Wilson, 2005), and by fulfilling motivational needs for self-esteem (Sedikides & Gebauer, 2010). However, the specific function that a religion serves differs between denominations, placing more or less emphasis on different beliefs and practices (Purzycki et al, 2016). In the present study we found that denominational differences in endorsement of religious beliefs and belief in predestination were related to prosociality.…”
Section: Discussionsupporting
confidence: 57%
“…Although previous studies have related the effects of religion on prosociality primarily to belief in a punishing God (Atkinson & Bourrat, 2011;Purzycki et al, 2016;Yilmaz & Bahcekapili, 2016), we found that Protestants (who donated more money) believed more strongly in a benevolent (vs. a punishing God) than Catholics. This finding is in line with more recent studies also showing that a benevolent view of God is associated with helping and benevolence toward outgroups (Johnson, Li, Cohen, & Okun, 2013;Johnson, Okun, & Cohen, 2015), suggesting that perceptions of God and Jesus may serve as a role model for moral behavior.…”
Section: Discussioncontrasting
confidence: 45%
“…Even if a correlation between cognitive reflection and religious disbelief turns out to be supported in North America, the degree to which such processes generalize widely beyond WEIRD (Western, Educated, Industrialized, Rich, Democratic: Henrich, Heine & Norenzayan, 2010) cultural contexts is still largely unknown. Certain features of religious beliefs vary strongly by culture (Purzycki et al, 2016), while others appear to be relatively stable (Gervais et al, 2017). It would be fortuitous and elegant if a parsimonious explanation of religious disbelief arising from cognitive reflection were generalizable to all or most cultures.…”
Section: Introductionmentioning
confidence: 99%